Ultrasound mediation of bioluminescence generated inside optically scattering media - Ahmad, Junaid (2019)
Bioluminescence imaging is a commonly used non-invasive technique in biology to access the pathological information in small animals. However, due to strong light scattering properties of biological tissue, it suffers a loss of spatial resolution and significant optical signal attenuation. Therefore, obtaining accurate information about physiology is challenging. This research proposes a hybrid imaging system that couples bioluminescence imaging with ultrasound (US) to offer a significant improvement in spatial resolution and quantitative accuracy of the imaging. This improvement is achieved using focused ultrasound that modulates the bioluminescence at US frequency (3.5 MHz) inside an optically scattering medium to produce an US switchable light ‘beacon’ that overcomes the influence of light scattering.